A formação pela trilha da clínica da atividade na vigilância em saúde do trabalhador - Luciano, Luzimar dos Santos (2014)
This work is a research-intervention study whose main objective is to analyze the activity in health surveillance anchored on the assumptions of formation through labor. This research was supported by the conceptual theoretical framework of the Clinic of activity proposed by Yves Clot et al. This study was performed with a multidisciplinary team that works in the Work’s Surveillance Reference Center of Espírito Santo State (Cerest/ES). The chat groups from the Clinic of Activity perspective were the prime methodological strategy. The activity surveillance genre in the professional worker’s health by confronting the study with the clinical guidelines of the activity, produced unfoldings that led the workers to ( re) think and analyze their activity, not to mention the working process in which they were involved. In every meeting in the dialog with the clinic of activity, not only ways on how they worked in the vigilance were experienced, but also the crossing of this kind of genre in assisting workers in educational activities and with the work management as well. As the chat groups were being developed, it was seen how these meetings have become a tool for those professionals. The activities developed produced a collective work analysis and a method of a forming process through activity. The workers sought to incorporate the methods used by the Clinic of Activity at Cerest’s day by day, dialoguing with the effects of this process. Furthermore, from the rounds of conversation proposals for changes in how the activities were taking place also emerged, as well as the work management in that working team and the strategies pursued in the surveillance, i.e., an intervention in the working group process, producing then potency to the acting power of the genre. Thus, we consider that the theoretical framework of the Clinic of Activity was a major training device. It allowed us an experimentation and development of a vigilant genre in occupational health in the production of activity analysis, and the establishment of a clinic in dialogical transformation as well. It also enabled us to contemplate in the analysis the integrating dimensions of the work activity, then promoting the communication channels for the meeting between the knowledge of experience established in the daily health service and the academic knowledge in knowledge production